URGENSI PERAN TANTANGAN DAN STRATEGI DALAM MENGHADAPI MASA DEPAN PENDIDIKAN INKLUSI: SYSTEMATIC LITERATURE REVIEW - Wijayanti, Wahyuni; Badu, Syamsu Qamar; Isa, Abd. Hamid; Zubaidi, Muhammad (Irfani, 2026)
This study aims to examine the roles, challenges, and strategies for the future of inclusive education in Indonesia through a Systematic Literature Review (SLR) of 30 relevant academic articles. The findings indicate that Special Education Schools (SLB) now play a crucial role as training centers, assessment service providers, and innovation hubs for regular schools. The primary challenges identified include human resource limitations, infrastructure gaps, policy inconsistencies, and socio-cultural barriers. Future strategies are focused on teacher competency development, the integration of assistive technology, and the creation of a collaborative educational ecosystem. The novelty of this research lies in the strategic repositioning of SLB, no longer merely as segregative institutions but as comprehensive resource centers that integrate assistive technology into a collaborative framework between the government and regular schools. These findings provide a foundation for policymakers to formulate more technical regulations regarding the standardization of SLB as national inclusion support centers to ensure equal educational rights for all children with special needs.